The relationship between wasting and stunting: a retrospective cohort analysis of longitudinal data in Gambian children from 1976 to 2016 - Schoenbuchner, Simon M; Dolan, Carmel; Mwangome, Martha; Hall, Andrew; Richard, Stephanie A; Wells, Jonathan C; Khara, Tanya; Sonko, Bakary; Prentice, Andrew M; Moore, Sophie E (The American journal of clinical nutrition, 2019)
The etiologic relationship between wasting and stunting is poorly understood, largely because of a lack of high-quality longitudinal data from children at risk of undernutrition. The aim of this study was to describe the interrelationships between wasting and stunting in children aged <2 y. This study involved a retrospective cohort analysis, based on growth-monitoring records spanning 4 decades from clinics in rural Gambia. Anthropometric data collected at scheduled infant welfare clinics were converted to z scores, comprising 64,342 observations on 5160 subjects (median: 12 observations per individual). Children were defined as “wasted” if they had a weight-for-length z score <–2 against the WHO reference and “stunted” if they had a length-for-age z score <–2. Levels of wasting and stunting were high in this population, peaking at approximately (girls–boys) 12–18% at 10–12 months (wasted) and 37–39% at 24 mo of age (stunted). Infants born at the start of the annual wet season (July–October) showed early growth faltering in weight-for-length z score, putting them at increased risk of subsequent stunting. Using time-lagged observations, being wasted was predictive of stunting (OR: 3.2; 95% CI: 2.7, 3.9), even after accounting for current stunting. Boys were more likely to be wasted, stunted, and concurrently wasted and stunted than girls, as well as being more susceptible to seasonally driven growth deficits. We provide evidence that stunting is in part a biological response to previous episodes of being wasted. This finding suggests that stunting may represent a deleterious form of adaptation to more overt undernutrition (wasting). This is important from a policy perspective as it suggests we are failing to recognize the importance of wasting simply because it tends to be more acute and treatable. These data suggest that stunted children are not just short children but are children who earlier were more seriously malnourished and who are survivors of a composite process.